5‐aza‐2'‐deoxycytidine may regulate the inflammatory response of human odontoblast‐like cells through the NF‐κB pathway. (4th March 2021) - Feng, Z.; Meng, R.; Li, Q.; Li, D.; Xu, Q.
Abstract: Aim: To explore the role of DNA methylation in the innate immunity of the dental pulp, this study investigated the effect of 5‐aza‐2'‐deoxycytidine (AZA) on lipoteichoic acid (LTA)‐induced cytokine production and related intracellular signalling pathways in human odontoblast‐like cells (hOBs). Methodology: hOBs were cultured and differentiated from human dental pulp tissue, and the odontoblastic phenotype of the cells was detected using immunofluorescence, qRT‐PCR and Western blotting. hOBs were pretreated with AZA and then stimulated with 10 μg mL −1 LTA. The levels of 42 cytokines related to immunity and inflammation were examined using a cytokine antibody array and verified using qRT‐PCR and ELISA. The effect of AZA on the LTA‐induced NF‐κB and MAPK signalling pathways was explored using Western blotting. The cells were treated with the specific NF‐κB inhibitor PDTC and MAPK inhibitors (the ERK inhibitor U0126, the p38 inhibitor SB203580, and the JNK inhibitor SP600125) to further confirm the role of the signalling pathways in LTA‐treated hOBs. DNA immunoprecipitation–PCR was used to examine the dynamic methylation status of the gene promoters of myeloid differentiation primary response 88 (MyD88) and tumour necrosis factor receptor‐associated factor 6 (TRAF6) in the LTA‐induced hOBs. Statistical analyses of the differences between two groups were performed using Student's t‐test. One‐way analysis of variance (anova ) or repeated‐measures anova with a post hoc Dunnett's test was used to assess the differences between multiple sets of data. P < 0.05 was considered to be statistically significant. Results: The odontoblastic markers were significantly higher in hOBs than those in human dental pulp cells (hDPCs) ( P < 0.05). According to the cytokine antibody array results, hOBs pretreated with AZA had significantly increased production of several inflammatory cytokines ( P < 0.05), in which the expression levels of IL‐6 and IL‐8 were the most dramatically increased upon LTA stimulation ( P < 0.01). Furthermore, AZA resulted in the significant upregulation of p‐IKKα/β, p‐IκBα, p‐p65, p‐p38 and p‐ERK in LTA‐stimulated hOBs ( P < 0.01). Treatment with the NF‐κB pathway inhibitor suppressed both IL‐6 and IL‐8 expression ( P < 0.05), whereas inhibitors of the MAPK pathway (SB203580 and SP600125) did not. In LTA‐treated hOBs, AZA significantly increased the expression levels of TRAF6 and MyD88 ( P < 0.05). AZA induced MyD88 promoter hypomethylation but did not affect TRAF6 methylation. Conclusion: AZA regulated the LTA‐induced inflammatory response through the NF‐κB signal pathway in hOBs. This study highlights the important role of DNA methylation in the immunity defence of odontoblasts during the dental pulp immunity response to caries.